Purification and Biochemical Characterization of Polyphenol Oxidase from Alanya Banana (Musa carevendishi) - KARAKUS*, EMINE; PEKYARDIMCI, SULE (Asian Journal of Chemistry, 2010)
Polyphenol oxidase was isolated from Alanya banana (Musacarevendishi) fruit grown in Southern Turkey with ammonium sulfateprecipitation and dialysis method. One protein fraction was obtainedwith gel filtration chromatography. Optimum temperature for bananapolyphenol oxidase was 25 °C with catechol substrate. Polyphenoloxidase showed maximum activity at pH 7.0 with catechol, caffeic acid,pyrogallol, 7.2 with 4-methylcatechol, 7.4 with L-tyrosine, 7.8 withp-cresol, 8.0 with gallic acid. Km and Vmax values in the case of 20 mMcatechol as substrate were 15.95 mM and 1776 ΔA min-1, respectively.Six different inhibitor were tested in this study and the most effectiveinhibitors for banana polyphenol oxidase were found to be L-cysteine,β-mercaptoethanol and sodium diethyldithiocarbamate. Inhibitionconstants (Ki) were calculated for every inhibitor at optimum pH of polyphenoloxidase activity. Polyphenol oxidase isoforms were determinedby using the partially purified banana polyphenol oxidase. Polyphenoloxidase isoforms migrated as 4 active bands with catechol substrate,4 bands with Coomassie Brillant R-250 during native polyacrylamidegel electrophoresis (N-PAGE). On the SDS-PAGE, banana polyphenoloxidase produced 5 bands of ca. 105 kDa, 52 kDa, 26 kDa, 18 kDa and15 kDa molecular weights. The activation energy, inactivation rate constantand half-lives (t1/2) of polyphenol oxidase were also calculated.